Prostate response to prolactin in sexually active male rats - Garcia Luis I; Toledo Rebeca; Aranda-Abreu Gonzalo E; Pascual Luz I; Rojas Fausto; Soto-Cid Abraham; Hernandez Maria; Quintanar-Stephano Andres; Manzo Jorge (BMC, 2006)
Abstract Background The prostate is a key gland in the sexual physiology of male mammals. Its sensitivity to steroid hormones is widely known, but its response to prolactin is still poorly known. Previous studies have shown a correlation between sexual behaviour, prolactin release and prostate physiology. Thus, here we used the sexual behaviour of male rats as a model for studying this correlation. Hence, we developed experimental paradigms to determine the influence of prolactin on sexual behaviour and prostate organization of male rats. Methods In addition to sexual behaviour recordings, we developed the ELISA procedure to quantify the serum level of prolactin, and the hematoxilin-eosin technique for analysis of the histological organization of the prostate. Also, different experimental manipulations were carried out; they included pituitary grafts, and haloperidol and ovine prolactin treatments. Data were analyzed with a One way ANOVA followed by post hoc Dunnet test if required. Results Data showed that male prolactin has a basal level with two peaks at the light-dark-light transitions. Consecutive ejaculations increased serum prolactin after the first ejaculation, which reached the highest level after the second, and started to decrease after the third ejaculation. These normal levels of prolactin did not induce any change at the prostate tissue. However, treatments for constant elevations of serum prolactin decreased sexual potency and increased the weight of the gland, the alveoli area and the epithelial cell height. Treatments for transient elevation of serum prolactin did not affect the sexual behaviour of males, but triggered these significant effects mainly at the ventral prostate. Conclusion The prostate is a sexual gland that responds to prolactin. Mating-induced prolactin release is required during sexual encounters to activate the epithelial cells in the gland. Here we saw a precise mechanism controlling the release of prolactin during ejaculations that avoid the detrimental effects produced by constant levels. However, we showed that minor elevations of prolactin which do not affect the sexual behaviour of males, produced significant changes at the prostate epithelium that could account for triggering the development of hyperplasia or cancer. Thus, it is suggested that minute elevations of serum prolactin in healthy subjects are at the etiology of prostate abnormal growth.